Aircraft timely departure probability technique calculation - S. V. Nikolaev (Научный вестник МГТУ ГА)
The article proposes the probability determination technique of timely aircraft departure, which is based on mathematical modeling method. It is proposed to use the indicator of timely departure probability, a calculation method of which is different from the known methods by taking into account the aircraft maintenance and repair system. This technique applies modern information technologies and the adopted approach is also supplemented with the mathematical model software implementation. The method of aircraft timely departure probability calculation is based on the model of the aircraft maintenance and repair system, utilizing the theory of mass service mathematical apparatus. The technique allows us to achieve the practical objectives of flight tests implementing aircraft maintainability evaluation and also complements the existing methodological support of the tests. The developed computer program provides the calculation of the required indicators for various values and combinations of factors which influence the result. Modeling was performed, and the study results of the main factors of probability effect, influencing timely departure are presented. Eventually the basic laws in solving the problem of aircraft timely departure, including interception of flying object are established.